BOUNDARY VALUE PROBLEM WITH SHIFT FOR TWO SIMPLE CONNECTED REGIONS - Damjanović, B. (Matematichki Bilten, 1996)
In this paper it is considered a boundary value problem for two analytic functions in different simple connected regions. If index corresponded to the problem is not greater then zero that it is shown solvable of that problem without any conditions and its solution is given by (4) in explicite form. If however the index is greater then zero then problem is solvable and its solution is given by (5) if real conditions of solvability (6) hold.